A NATO for the 21st Century: Toward a New Strategic Concept - Shea, Jamie (Tufts Archival Research Center, 2005)
Volume 31, Issue 2. Summer NATO will mark its 60th anniversary in 2009, but celebrations are meaningless without a continuing sense of purpose. NATO's ongoing mission in Afghanistan, its efforts to combat terrorism and WMD proliferation, and its humanitarian relief capabilities, among other things, will continue to be critical to the security of its member states and the broader regions within which the Alliance operates. A new Strategic Concept clearly outlining NATO's 21st century roles may be in order.